Por uma efetiva construção da igualdade de gênero no ordenamento jurídico brasileiro: análise da necessária revisão do tratamento diferenciado à mulher nas aposentadorias por idade e por tempo de contribuição na Constituição Federal de 1988 - Andreucci, Ana Cláudia Pompeu Torezan (2010)
The present work has for objective to analyze a present affirmative action in the Federal Constitution of 1988 granting favorably to held them of the general regime of Social welfare Brazilian retirement for age and for time of contribution with smaller time in relation to the masculine universe. Such an affirmative action was instituted by the Brazilian legislator leaving of premises that now no more they are justified, which are, the woman's biological fragility and the need of compensation of the time of work in reason of the couple day understood as the professional work (public sphere) and the domestic work (deprived sphere). it will Be focused that such an affirmative action doesn't rescue the necessary equality among men and women, position that the woman is going through the juridical own Brazilian Laws receiving outlines protectionists and that no truth is pseudo-protections social, responsible for the maintenance of the gender inequality, in the measure in that you/they reinforce the traditional theory of the woman's lonely responsibility in the space of the private life. To defends in the present work not for the mere extinction of a right, but, for the substitution of the benefit of social security above mentioned by another benefit denominated license-parental capable to generate it executes gender equality in the Brazilian Laws, in the molds that it is already happening in Europe, reached her, for consequence road, the larger objectives declared by the Democratic State of Right, the justice and the social well-being